FEATURES OF COVID-19 THERAPY IN PATIENTS WITH CHRONIC DISEASES - Usmanova E.M. (Western European Studies, 2024)
To study the effect of drugs on the severity and outcome of the disease used in the treatment of patients with concomitant diseases during COVID-19 infection. Materials and methods of research. The study included 453 patients with COVID-19, of which 370 (81.8%) were hospitalized in the infectious diseases hospital of Andijan region and 82 (18.2%) received outpatient treatment. Study results and discussion: 79.8% of patients under observation have concomitant diseases. Due to the regular use of drugs taken by patients with concomitant diseases in the period before infection, it influenced the development and outcome of COVID-19. Conclusion. According to our observations, the majority of patients with COVID-19 have concomitant diseases, among which diseases of the circulatory system predominate. Taking statins in patients with coronary artery disease had a beneficial effect on the prognosis of COVID-19 and was associated with a reduced risk of death
Keywords: Covid-19; coronary heart disease; chronic obstruction of the lungs